A Systematic Review of Learning Media Research Trends From 2011 to 2021 - Zahroni, Siti (Tauladan Fathimah Azzahra, 2022)
Several literature review studies analyze trends in using digital learning media in educational process. This goes hand in hand, with the development of ICT in all areas of life. In the literature, learning media by teachers have an important role in the learning and education process. The purpose of this study is to analyze the published literature on learning media through a systematic literature review. A total of 135 articles have been selected for review and analysis from the Springer database published from 2011 to 2021 or the last 10 years. This study analyzes the distribution frequency of publications by year, the number of authors in publication, the top journals with the highest number of articles, and the most productive countries in learning media research. The results of the study show that learning media has become a concern of researchers in the last decade, where taking into account the annual volume of Learning Media research, the results of the analysis show that the number of articles tends to fluctuate with the peak of publication in 2021, that is 123 articles. The largest percentage in the number of authors was recorded in articles with 3 authors, that is 31.11% or 42 articles. In the analysis of the top 10 publishers, the largest percentage was in articles published by Technology, Knowledge and Learning with 26 articles or 21.13%, then TechTrends, and Educational Technology Research and Development which seemed to be the journals with the most articles published. In addition, if sorted by country, the United States has the highest contribution and followed by Turkey, Taiwan, Spain, Sweden compared to other countries in learning media research around the world